Absorptive capacity and the diffusion of innovation in NTBFs and startups: A study in the Brazilian Federal District - Pereira, Bruno Alencar; Farias, Josivania Silva (REGEPE Entrepreneurship and Small Business Journal, 2023)
Purpose: To verify the contribution of the Absorptive Capacity (ACAP) to the diffusion of innovation in New Technology-Based Firms (NTBFs) and startups in the Brazilian Federal District. Method: In-depth interviews study with 20 innovative firms, 12 (twelve) startups and 8 (eight) NTBFs. The results are discussed in two items of analysis: Analysis of the profile of the firms and the Analysis of the Descending Hierarchical Classification (DHC) and of the content, in a comparative perspective around 14 thematic categories. Findings: The development factors associated with the Potential of Absorptive Capacity (PACAP) were observed as the antecedents of the diffusion of innovation. On the other hand, factors related to the Realized Absorptive Capacity (RACAP) are involved directly in the diffusion of innovation, with emphasis on the ability to generate innovation results through channels of market introduction, adoption of new technologies and financial investments. Theoretical/methodological contributions: The study contributes to the theoretical field, still lacking in production, especially regionally, on the relationship between the constructs investigated in the context of innovative firms. Supporting programs, can gain insights to improve the advanced support that facilitates access to knowledge to be adopted and conversion into innovation. Relevance/originality: The research extends the understanding of the relationship between ACAP and the diffusion of innovation, involving the absorption of knowledge and the dynamics of these constructs through the integration of critical factors in specific contexts still little investigated, such as in NTBFs and startups involving regional innovation ecosystems. Management/Social Contributions: The empirical investigation and factors addressed provide managerial implications for the practices of these firms when developing innovations, as well as for planning, developing or strengthening innovation programs and policies.